GNN model for classification of SARS-CoV-2 severity in molecules - Delower, H M Layes; Tanzim, Khandakar Maisha; Shahriar, Faisal; Fairooz, Sharika (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.